Tinjauan Yuridis Pencabutan Hak Kewarganegaraan Mantan Anggota Organisasi Militan Ekstremis (ISIS) Perspektif Hukum Internasional dan Aturan Kewarganegaraan - Abdullah Raden Aji Haqqi; Rohmad Adi Yulianto; Damrah Mamang (VERITAS, 2021)
Citizenship is a legal bond between a person and a country. Citizenship gives people an identity. According to the Universal Declaration of Human Rights affirms that "everyone has the right to a nationality", thus this declaration recognizes the importance of citizenship legally and practically for the fulfillment of human rights. Therefore, governments must work to ensure that everyone has a nationality. Former members of extremist militant organizations themselves can be interpreted as military groups (Army, Navy and Air Force), and militias and volunteer corps that meet these four requirements, are called “Former members”. They are justified in actively participating in hostilities. Also included in the ex-member group are: residents of an area that has not been occupied by the enemy, who spontaneously took up arms when organizing themselves, and carried weapons openly. Extremism is not really new. There has been a lot of extremist behavior that is usually associated with terrorist behavior and attacks against a group, both in Indonesia and abroad. Extremist behavior is slightly different from criminal behavior in general. The crimes committed by extremists are crimes based on the path they have chosen regarding their way of seeing the world. Law number 12 of 2006 concerning citizenship, it is stated in article 23 that Indonesian citizens will lose their citizenship in several ways, starting from the person concerned obtaining another citizenship, entering the service of a foreign army, entering the service of a foreign country, swearing allegiance to a foreign country. , participating in the elections of foreign countries, and several other matters mentioned in Chapter IV of the law. So even though it is true that ISIS itself is not a country as described in the writing of this thesis, this cannot be used as a basis for guiding that an Indonesian citizen who is a member of ISIS cannot lose his citizenship because it is clearly regulated in both laws and regulations. The government is what causes the Indonesian citizen to lose his citizenship automatically, not because of certain individuals who can decide whether or not a person's citizenship is lost or not.